Conférences internationales - Trébuchon, JF (BOIS & FORETS DES TROPIQUES, 2020)
4 th World Teak Conference – Global Teak market: Challenges and Opportunities for emerging markets and developing economics. Accra, Ghana. August 23-26, 2021. In 2020, Ghana will host the 4th World Teak Conference, for the first time in Africa. This event will take place in Kempinski Hotel, Accra, Ghana during 23-26 August 2021, and will be organized and coordinated by the International Teak Information Network (TEAKNET),India and hosted by the Forestry Commission, Ghana. The past three World Teak Conferences were held in Asian and Latin American countries to: the first one in Costa Rica (2011), followed by Bangkok (2013) and Ecuador (2015). In Ghana teak is reported to have been introduced as early as in 1905 and constitutes 70% of all plantation species in the country. The total area of teak plantations is currently estimated at 180,000 ha of which 60% is owned by the public sector with the remaining by the private sector. This is a world-class event and will be an extremely interesting and valuable conference expected to attract over 300 participants.The Conference will be a great opportunity to exchange knowledge and experiences on technological innovations and stay up to date on the emerging trends in teak management and trade. It will provide a major meeting place for worldwide researchers, students, entrepreneurs and professionals in the forestry sector to come together, share their knowledge and establish networks. Theme The 4th World Teak Conference with the theme –‘Global Teak Market: Challenges and Opportunities for Emerging Markets and Developing Economies’ will address the most crucial issues of the global teak sector including: Sustainable management of smallholder teak farming systems for quality supply of teak timber to market. Review and improvement of existing silvicultural systems and practices for better stand management on teak wood quality. Analysis of market structures and value chains of teakwood trading and their impact on the profitability of teak investments. Evaluation of private and public investments in the teak sector and its impacts on socio-economic conditions and rural livelihoods. Developing strategic, conceptual and operational recommendations in support of the sustainable development of the teak sector. https://www.worldteakconference2020.com/theme/